CO2 methanation over heterogeneous catalysts: recent progress and future prospects. Issue 5 (12th May 2015) - Aziz, M. A. A.; Jalil, A. A.; Triwahyono, S.; Ahmad, A.
<x xml:space="preserve">Abstract</x> This review describes an overview on much of the recent work in catalytic methanation of CO2 and its future prospects.